2008
DOI: 10.1177/0731684408089489
|View full text |Cite
|
Sign up to set email alerts
|

Wear Mechanism of Glass Fiber Reinforced Epoxy Composites Under Dry Sliding Using Fuzzy Clustering Technique

Abstract: Polymers and polymer composites are steadily gaining ground over metals in the field of engineering applications in tribology. In the present study, the friction and wear behavior of glass fiberreinforced epoxy composites against stainless steel under dry sliding conditions has been comparatively evaluated on a friction and wear tester at different sliding velocities ranging from 0.6 to 2.5 m/s and normal force of 9.81 to 19.62 N. Besides, conventional weighing, determination of coefficient of friction (), tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Signifying a considerable amount of abrasive wear and fatigue wear. Therefore, the wear mechanism is a combination of fatigue and abrasive wear for Thordon SXL [ 32 ]. Few smooth scratches are observed on the wear surfaces of BTG rubber, so its wear mechanism is abrasive wear.…”
Section: Resultsmentioning
confidence: 99%
“…Signifying a considerable amount of abrasive wear and fatigue wear. Therefore, the wear mechanism is a combination of fatigue and abrasive wear for Thordon SXL [ 32 ]. Few smooth scratches are observed on the wear surfaces of BTG rubber, so its wear mechanism is abrasive wear.…”
Section: Resultsmentioning
confidence: 99%
“…Other experimental studies that utilized this method of calculating COF have reported a similar relationship between COF and normal force. [12][13][14] The higher contact stresses that the pads experienced under increasing normal forces likely caused increased deformation at local contact points, thus changing the geometry of the contact and altering the shear behavior of the material. When the pressure exceeds a critical value that is based on the strength of a material, the friction and wear behavior of the polymer materials is affected.…”
Section: Resultsmentioning
confidence: 99%
“…Also, it is concluded that the volume fraction of fibres, orientation of fibres and different sliding conditions are majorly noted to control the wear rate of the composites. 108 Analysis of variance (ANOVA) is another important analysis used to know the significant factors and contribution of each factor in an engineering problem. 109 A study on the tribological behaviour of glass reinforced-PEEK composites used and Taguchi and ANOVA for analysis.…”
Section: Statistical Tools For Tribological Assessment Of Frpmentioning
confidence: 99%